2018
DOI: 10.3390/nu10091232
|View full text |Cite
|
Sign up to set email alerts
|

“Your Body Feels Better When You Drink Water”: Parent and School-Age Children’s Sugar-Sweetened Beverage Cognitions

Abstract: Sugar-sweetened beverages (SSBs) are a leading source of added sugar in the American diet. Further, ingestion of added sugars from SSBs exceeds recommendations. Thus, interventions that effectively reduce SSB consumption are needed. Focus group discussions with parents (n = 37) and school-aged children between the ages of 6 and 11 years (n = 41) from Florida, New Jersey, and West Virginia were led by trained moderators using Social Cognitive Theory as a guide. Trends and themes that emerged from the content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…In several cases, CSSBs were available because parents or other family members consumed these beverages. This finding is supported by a large body of research underscoring the importance of caregivers' modeling in influencing child dietary behaviors [20,25]. Most parents acknowledged the contribution of their own CSSB consumption to their child's intake, and several reported feeling guilt for introducing CSSBs and/or making them available in the home.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In several cases, CSSBs were available because parents or other family members consumed these beverages. This finding is supported by a large body of research underscoring the importance of caregivers' modeling in influencing child dietary behaviors [20,25]. Most parents acknowledged the contribution of their own CSSB consumption to their child's intake, and several reported feeling guilt for introducing CSSBs and/or making them available in the home.…”
Section: Discussionmentioning
confidence: 70%
“…Parental awareness of negative health effects associated with excessive sugar intake has been documented previously [20], specifically with regard to weight gain [21]. Concern regarding child hyperactivity and sleep problems resulting from SSB intake (not specific to CSSBs) have also been previously reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the extinction of conditioned voluntary water consumption, and the failure to ingest orally perfused water could represent the development of an aversion to the previously neutral water in parallel to the learned preference for sucrose. Given the positive association between the preference for sweet drinks and the frequency of their consumption [33] our findings have implications for strategies to reduce the consumption of sugarsweetened beverages, particularly in young children and adolescents [27].…”
Section: Discussionmentioning
confidence: 85%
“…The food industry is responding to consumer desire to lower added sugar, while maintaining product palatability, but from the standpoint of a consumer packaged goods company, there are numerous issues to consider. These include guidance to reduce added sugar from public health organizations , proposed changes to the nutrition facts panel, proposed policies to reduce added sugar intake such as SSB taxes , and consumer desire to reduce added sugar intake , all reiterating the need to lower product sugar content. However, while there is significant pressure to reduce sugar and while consumers express a desire to avoid artificial sweeteners, the International Food Information Council (IFIC) 2017 Food and Health survey revealed that ‘taste’ remains a key driver of food selection and consumer purchasing decisions .…”
Section: Seminar 3: Are Added Sugar Alternatives or Other Novel Ingrementioning
confidence: 99%